One Week of Motor Adaptation Induces Structural Changes in Primary Motor Cortex That Predict Long-Term Memory One Year Later - Landi, Sofía Mariana (2011)
The neural bases of motor adaptation have been extensively explored in human and non-human primates. A network including the cerebellum, primary motor and the posterior parietal cortex appears to be crucial for this type of learning. Yet, to date, it is unclear whether these regions contribute directly or indirectly to the formation of motor memories. Here we trained subjects on a complex visuomotor rotation associated with long-term memory (in the order of months) to identify potential sites of structural plasticity induced by adaptation. One week of training led to i) an increment in local gray-matter concentration over the hand area of the contralateral primary motor cortex and ii) an increase in fractional anisotropy in an area underneath this region that correlated with the speed of learning. Moreover, the change in gray matter concentration measured immediately after training predicted improvements in the speed of learning during re-adaptation one year later. Our study suggests that motor adaptation induces structural plasticity in primary motor circuits. In addition, it provides the first piece of evidence indicating that early structural changes induced by motor learning may impact on behavior up to one year after training.